THIRD-PARTY IN INTERNATIONAL COMMERCIAL ARBITRATION: INDONESIA PERSPECTIVE - Prita Amalia; Muhammad Faiz Mufidi (Mimbar Hukum, 2023)
Abstract An arbitration Agreement between the parties is an important source of law in the arbitration proceeding, especially in International Commercial Arbitration. Arbitration Agreements, which could be made before and after the dispute, provide jurisdiction to the arbitral tribunal to settle the dispute. Traditionally, the arbitration agreement provides that only the parties in the agreement could be bound by the arbitration proceeding. However, in commercial arbitration, there is a circumstance in which a third party could be bound to arbitration proceedings. Indonesia has an arbitration law based on Law No. 30 Year 1999 concerning Arbitration and Alternative Dispute Resolution. This law stipulates how arbitration proceedings could proceed in Indonesia, including third-party issues in arbitration proceedings, as stipulated in Article 30. However, it depends on an arbitrator to settle since the Law itself does not explain further. The definition also does not govern in BANI Rules and Procedure as BANI procedural law. One opinion based on the writer’s research shows that commercial arbitration in Indonesia could also consider Indonesian Civil Procedural Law, as well as the regulation toward third parties’ involvement. Some of the mechanism of third parties’ involvement that has been regulated in Indonesian Civil Procedural Law is Vrijwaring, Tussenkomst, and Voeging. Abstrak Perjanjian Arbitrase di antara para pihak merupakan sumber hukum utama dalam proses arbitrase, khususnya dalam Arbitrase Komersial Internasional. Perjanjian Arbitrase dapat dibuat sebelum dan setelah sengketa, dan merupakan dasar kewenangan dari lembaga arbitrase untuk menyelesaikan sengketa. Secara konsep, perjanjian arbitrase hanya mengikat para pihak yang terikat dalam perjanjian arbitrase. Namun demikian, terdapat kondisi bilamana pihak ketiga dapat terikat dalam proses arbitrase. Indonesia mengatur arbitrase dalam UU No. 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa. Undang-undang ini mengatur bagaimana proses arbitrase di Indonesia, termasuk para pihak dalam proses arbitrase sebagaimana diatur dalam Pasal 30. Hal ini sangat tergantung pada arbiter untuk memutuskannya karena undang-undang tidak memberikan penjelasan lebih lanjut. Penjelasan selanjutnya juga tidak diatur dalam Hukum Acara BANI. Berdasarkan hasil penelitian yang dilakukan, dalam arbitrase komersial di Indonesia, para pihak perlu mempertimbangkan Hukum Acara Perdata yang berlaku di Indonesia, khususnya mengenai pengaturan bagaimana pihak ketiga bisa terikat dalam proses arbitrase. Mekanisme keterlibatan pihak ketiga yang diatur dalam Hukum Acara Perdata Indonesia yaitu Vrijwaring, Tussenkomst, and Voeging.